A neurobehavioral therapy approach to the rehabilitation and support of persons with brain injury: Practice-based evidence from a UK charitable rehabilitation provider - Rudi Coetzer; Rudi Coetzer; Rudi Coetzer; Sara da Silva Ramos; Sara da Silva Ramos (Frontiers Media S.A., 2022)
BackgroundThe treatment and rehabilitation for people with acquired brain injury is continually evolving, with increasing recognition of the importance of approaches that adopt a multi-disciplinary biopsychosocial perspective focused on improving adjustment, social participation, and wellbeing. However, there is significant variability as to how such approaches are delivered, across the various stages of recovery, rehabilitation settings, and within different healthcare systems.ObjectiveThis paper had three aims. The first was to describe the neurobehavioral therapy (NBT) approach to brain injury rehabilitation adopted in our charitable organization. The second aim was to report how the NBT approach evolved in response to changes in referral patterns, and patient needs within a broader, longer-term clinical pathway. The third aim was to assess the effectiveness of the NBT approach by analyzing outcome data.MethodsRetrospective analyses of standardized outcome data were completed to investigate the effectiveness of our approach. Case vignettes are provided to illustrate the key components of the approach.ResultsOutcome data suggested that the approach is effective in delivering positive outcomes for patients. Furthermore, the data show differences in presentation between three clinical streams (restoration, compensation, and scaffolding) within the NBT approach.ConclusionsThis paper describes the adaption of the 'traditional' neurobehavioral approach to brain injury rehabilitation into a model of delivery that can benefit a more diverse range of people living with the heterogenous and long-term consequences of brain injury.